Anti-PD-L1 immunoconjugates for cancer therapy: Are available antibodies good carriers for toxic payload delivering? - Zanello, Andrea; Bortolotti, Massimo; Maiello, Stefania; Bolognesi, Andrea; Polito, Letizia (Frontiers in Pharmacology, 2022)
Immune checkpoint mechanisms are important molecular cell systems that maintain tolerance toward autoantigens in order to prevent immunity-mediated accidental damage. It is well known that cancer cells may exploit these molecular and cellular mechanisms to escape recognition and elimination by immune cells. Programmed cell death protein-1 (PD-1) and its natural ligand programmed cell death ligand-1 (PD-L1) form the PD-L1/PD-1 axis, a well-known immune checkpoint mechanism, which is considered an interesting target in cancer immunotherapy. In fact, the expression of PD-L1 was found in various solid malignancies and the overactivation of PD-L1/PD-1 axis results in a poor patient survival rate. Breaking PD-L1/PD-1 axis, by blocking either the cancer side or the immune side of the axis, is currently used as anti-cancer strategy to re-establish a tumor-specific immune response. For this purpose, several blocking antibodies are now available. To date, three anti-PD-L1 antibodies have been approved by the FDA, namely atezolizumab, durvalumab and avelumab. The main advantages of anti-PD-L1 antibodies arise from the overexpression of PD-L1 antigen by a high number of tumor cells, also deriving from different tissues; this makes anti-PD-L1 antibodies potential pan-specific anti-cancer molecules. Despite the good results reported in clinical trials with anti-PD-L1 antibodies, there is a significant number of patients that do not respond to the therapy. In fact, it should be considered that, in some neoplastic patients, reduced or absent infiltration of cytotoxic T cells and natural killer cells in the tumor microenvironment or presence of other immunosuppressive molecules make immunotherapy with anti-PD-L1 blocking antibodies less effective. A strategy to improve the efficacy of antibodies is to use them as carriers for toxic payloads (toxins, drugs, enzymes, radionuclides, etc.) to form immunoconjugates. Several immunoconjugates have been already approved by FDA for treatment of malignancies. In this review, we focused on PD-L1 targeting antibodies utilized as carrier to construct immunoconjugates for the potential elimination of neoplastic cells, expressing PD-L1. A complete examination of the literature regarding anti-PD-L1 immunoconjugates is here reported, describing the results obtained in vitro and in vivo. The real potential of anti-PD-L1 antibodies as carriers for toxic payload delivery is considered and extensively discussed.